Clinical practice guidelines for the management of biliary tract cancers 2019: The 3rd English edition - Nagino, Masato; Hirano, Satoshi; Yoshitomi, Hideyuki; Aoki, Taku; Uesaka, Katsuhiko; Unno, Michiaki; Ebata, Tomoki; Konishi, Masaru; Sano, Keiji; Shimada, Kazuaki; Shimizu, Hiroaki; Higuchi, Ryota; et al. (Journal of hepato-biliary-pancreatic sciences, 2021)
Background The Japanese Society of Hepato‐Biliary‐Pancreatic Surgery launched the clinical practice guidelines for the management of biliary tract cancers (cholangiocarcinoma, gallbladder cancer, and ampullary cancer) in 2007, then published the 2nd version in 2014. Methods In this 3rd version, clinical questions (CQs) were proposed on six topics. The recommendation, grade for recommendation, and statement for each CQ were discussed and finalized by an evidence‐based approach. Recommendations were graded as Grade 1 (strong) or Grade 2 (weak) according to the concepts of the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. Results The 31 CQs covered the six topics: (a) prophylactic treatment, (b) diagnosis, (c) biliary drainage, (d) surgical treatment, (e) chemotherapy, and (f) radiation therapy. In the 31 CQs, 14 recommendations were rated strong and 14 recommendations weak. The remaining three CQs had no recommendation. Each CQ includes a statement of how the recommendations were graded. Conclusions This latest guideline provides recommendations for important clinical aspects based on evidence. Future collaboration with the cancer registry will be key for assessing the guidelines and establishing new evidence. Highlight These guidelines are the English version of “Evidence‐based clinical practice guidelines for the management of biliary tract cancers, 3rd edition” published in Japanese by the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery in 2019. A total of 31 clinical questions covering six topics provide recommendations for important clinical aspects based on evidence.